The expression that is not equivalent to the rest is:
17⋅m⋅7+7
Start Fraction 1 over 7 End Fraction times m times 7 plus 7
Expressions Unit Test
8 of 158 of 15 Items
Question
Which of the following expressions is not equivalent to the rest?(1 point)
Responses
5+m−12
5 plus m minus 12
17⋅m⋅7+7
Start Fraction 1 over 7 End Fraction times m times 7 plus 7
m⋅1+7
m times 1 plus 7
18+m−11
18 plus m minus 11
Skip to navigation
11 answers
Which of the following expressions is not equivalent to the rest?(1 point)
Responses
5+m−12
5 plus m minus 12
17⋅m⋅7+7
Start Fraction 1 over 7 End Fraction times m times 7 plus 7
m⋅1+7
m times 1 plus 7
18+m−11
Responses
5+m−12
5 plus m minus 12
17⋅m⋅7+7
Start Fraction 1 over 7 End Fraction times m times 7 plus 7
m⋅1+7
m times 1 plus 7
18+m−11
The expression that is not equivalent to the rest is:
18+m−11.
18+m−11.
Complete the following stepped-out solution to show that 15+g+32⋅23 is equivalent to 16+g .(1 point)
15+g+32⋅23
15+g+
Inverse Property of Multiplication
15+
+g Commutative Property of Addition
16+g Addition
15+g+32⋅23
15+g+
Inverse Property of Multiplication
15+
+g Commutative Property of Addition
16+g Addition
15+g+32⋅23
= 15+g+(32⋅23)
= 15+g+(736)
= 15+g+736
= (15+736) + g
= 751 + g
= 16 + g
Therefore, 15+g+32⋅23 and 16+g are equivalent expressions.
= 15+g+(32⋅23)
= 15+g+(736)
= 15+g+736
= (15+736) + g
= 751 + g
= 16 + g
Therefore, 15+g+32⋅23 and 16+g are equivalent expressions.
simplify it
To simplify the expression 15+g+32⋅23, we can perform the multiplication first and then combine like terms:
32⋅23 = 736
Now, we can rewrite the expression:
15+g+736
Since there are no like terms to combine, the simplified expression is:
751+g
32⋅23 = 736
Now, we can rewrite the expression:
15+g+736
Since there are no like terms to combine, the simplified expression is:
751+g
Expressions Unit Test
10 of 1510 of 15 Items
Question
Complete the following stepped-out solution to show that −7+[(8⋅m)⋅18]+7 is equivalent to m . (2 points)
−7+
+[(8⋅m)⋅18] Commutative Property of Addition
+[(8⋅m)⋅18] Inverse Property of Addition
(8⋅m)⋅18 Identity Property of Addition
(8⋅
)⋅ m Associative Property of Multiplication
(
)⋅m Inverse Property of Multiplication
m Identity Property of Multiplication
Skip to navigation
10 of 1510 of 15 Items
Question
Complete the following stepped-out solution to show that −7+[(8⋅m)⋅18]+7 is equivalent to m . (2 points)
−7+
+[(8⋅m)⋅18] Commutative Property of Addition
+[(8⋅m)⋅18] Inverse Property of Addition
(8⋅m)⋅18 Identity Property of Addition
(8⋅
)⋅ m Associative Property of Multiplication
(
)⋅m Inverse Property of Multiplication
m Identity Property of Multiplication
Skip to navigation
−7+[(8⋅m)⋅18]+7
Using the Commutative Property of Addition:
−7+[(8⋅m)⋅18]+7 = −7+7+[(8⋅m)⋅18]
Using the Inverse Property of Addition:
−7+7+[(8⋅m)⋅18] = 0+[(8⋅m)⋅18]
Using the Identity Property of Addition:
0+[(8⋅m)⋅18] = (8⋅m)⋅18
Using the Associative Property of Multiplication:
(8⋅m)⋅18 = 8⋅(m⋅18)
Using the Inverse Property of Multiplication:
8⋅(m⋅18) = 8⋅m
Using the Identity Property of Multiplication:
8⋅m = m
Therefore, −7+[(8⋅m)⋅18]+7 is equivalent to m.
Using the Commutative Property of Addition:
−7+[(8⋅m)⋅18]+7 = −7+7+[(8⋅m)⋅18]
Using the Inverse Property of Addition:
−7+7+[(8⋅m)⋅18] = 0+[(8⋅m)⋅18]
Using the Identity Property of Addition:
0+[(8⋅m)⋅18] = (8⋅m)⋅18
Using the Associative Property of Multiplication:
(8⋅m)⋅18 = 8⋅(m⋅18)
Using the Inverse Property of Multiplication:
8⋅(m⋅18) = 8⋅m
Using the Identity Property of Multiplication:
8⋅m = m
Therefore, −7+[(8⋅m)⋅18]+7 is equivalent to m.
answer the question above
The stepped-out solution shows that -7+[(8⋅m)⋅18]+7 is equivalent to m.